Labor Market Strength and Declining Community College Enrollment - Joshua Goodman; Joseph Winkelmann (Institute of Labor Economics (IZA), 2025)
Declining U.S. college enrollments over the past 15 years have triggered questions about the health of the postsecondary sector. Using college-level data, we make four points. First, such declines are driven not by the 4-year sector but by 2-year community colleges, which have apparently shrunk by over 30% since the Great Recession's peak. Second, one-third of this apparent decline is an artifact of some community colleges being reclassified as offering 4-year degrees. Third, pre-Great Recession data shows a 1 percentage point increase in local unemployment rates increases first-time community college enrollment by 2%, suggesting many students are on the margin between community college and job opportunities. For-profit college enrollments are also countercyclical, while 4-year college enrollments are acyclical. Our estimates suggest strengthening labor markets explain 60% of the post-Great Recession decline in first-time community college enrollment. Fourth, students whose enrollment decisions are most sensitive to labor market conditions are unlikely to have completed degrees. Though declining enrollments are a challenge for community colleges, it is unclear whether they are problematic for students on the margin of enrollment.
Keywords: I23; J24; 330; community college; labor market conditions; unemployment rate